PERLINDUNGAN HUKUM TERHADAP KEAMANAN DAN KESELAMATAN WISATAWAN DI BATU BENGKUNG KABUPATEN MALANG - Phetricia, Shilvia Audy; Borman, M. Syahrul; Boerhan, Soebagio; Subekti, Subekti (UNES Law Review, 2023)
Tourism is the activity of temporary travel of one or more people to a location other than their place of residence. In Batu Bengkung, residents depend on tourism for their livelihood. This study discusses legal protection for tourists by focusing on two aspects. First, Law no. 10 of 2009 concerning Tourism regulates legal protection for tourists and tourism industry players in the event of loss from both parties. Second, the manager's obligation to guarantee the security and safety of Batu Bengkung beach visitors if an incident occurs. The research method used is an empirical research technique with a sociological legal perspective. The results of the study show that Law Number 10 of 2009 concerning Tourism provides fair protection for travelers and tourism industry players. This protection covers the full rights and obligations of both parties. The responsibility of the manager for the safety and security of Batu Bengkung Beach tourists is to provide insurance claims and hospital medical expenses for victims.